Analisis Keterampilan Bertanya pada Pembelajaran IPA Siswa Kelas VIII SMP N Sumber Harta - R. A. Ramadhona; Ahmad Amin (Journal on Education, 2024)
The aim of this research is to analysis the questioning skilla of clas VIII students at SMP Negeri Sumber Harta in science learning. In this research, descriptive research methods were used usinga qualitative apporoac, with instruments in the form of observation sheets and interview sheets. The subjectsbin this research were science subject teachers and students of class VIII SMP Negeri Sumber Harta with a sample of 4 students out of 31 students. The results of the analysis of sudents questioning skills in science learning are in the medium category. It can be concluded that students with high ability think science learning is easy, but students with medium ability think science is not too difficult, and students with low ability think it is difficult.